Monday

July 28, 2014

July 28, 2014

Posted by **Aria** on Tuesday, June 5, 2012 at 12:12am.

- Calculus -
**Steve**, Tuesday, June 5, 2012 at 12:16am2xy^3 + 3x^2y^2y' + 3x^2y^4 + 4x^3y^3y' = 0

y' = -(2xy^3 + 3x^2y^4)/(3x^2y^2 + 4x^3y^3)

= -(2y + 3xy^2)/(3x + 4x^2y)

assuming x,y not zero

- Calculus -
**Aria**, Tuesday, June 5, 2012 at 12:22amThanks a lot, it makes so much more sense now! :)

**Related Questions**

Vector Calculus - Thermodynamics texts use the relationship (dy/dx)(dz/dy)(dx/dz...

Math (Calculus II) - Rate of change proportional to size: P(t)= P(i)e^kt, where ...

Math (Calculus II) - Rate of change proportional to size: P(t)= P(i)e^kt, where ...

Calculus - Determine the intervals on which the function is concave up and ...

Derivative - implicitly differentiate f(x) 2xy= y ^2 find second derivative with...

Calculus - Follow the steps below for the given function. (Do not use mixed ...

calculus - find dx/dy implicitly from √(x+y) = 1 + (x^2)(y^2). then solve ...

calculus - find dx/dy implicitly from √(x+y) = 1 + (x^2)(y^2). then solve ...

trigo help! - 1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. ...

AP calculus - Find (dy/dx) for the following implicitly defined function: 2x = ...